Improved on-state performance in AlGaN-channel heterojunction field-effect transistors with a quaternary AlGaInN barrier layer and a selectively grown n++-GaN contact layer. (October 2021) - Miyoshi, Makoto; Inoue, Akiyoshi; Yamanaka, Mizuki; Harada, Hiroki; Egawa, Takashi
Abstract: Al0.19 Ga0.81 N-channel metal-insulator-semiconductor heterojunction field-effect transistors (MIS-HFETs) with a quaternary AlGaInN barrier layer and a selectively regrown n ++ -GaN contact layer were fabricated using the self-alignment selective-area growth (SAG) technique. The self-alignment SAG process was accomplished by the local-area etching process and the subsequent refilling process with a highly-Si-doped n ++ -GaN layer by metalorganic chemical vapor deposition (MOCVD). It was confirmed that the ohmic contact resistance was drastically reduced from 10.5 Ωmm to 2.5 Ωmm via the self-alignment SAG contacts. Further, fabricated MIS-HFETs with a gate length of 1.5 μm and a drain-to-source length of 9.5 μm exhibited a high drain current density of over 300 mA/mm with a drain-to-source resistance of approximately 25 Ω mm. The fabricated devices also showed a high off-state breakdown voltage of 1220 V at a gate-to-drain length of 10 μm, corresponding to a breakdown field of 122 V/μm.